2022
DOI: 10.1186/s12969-022-00728-0
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology, clinical manifestations and current management of IL-1 mediated monogenic systemic autoinflammatory diseases, a literature review

Abstract: Background Systemic autoinflammatory diseases (SAIDs) are hyperinflammatory and immune-dysregulation conditions that present in childhood. This kind of disease is a rare disease with early-onset, severe condition and difficult diagnosis, which seriously affects the growth and development of children. Most children need a genetic diagnosis. However, with the limitation of access to genetic testing and the detection of somatic mutations, the diagnosis of SAIDs remains challenging. IL-1 is one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 85 publications
0
4
0
1
Order By: Relevance
“…The clinical use of this bioagent in MKD has been approved with satisfactory results leading to a disappearance or a significant reduction in the severity of MKD features, including fever, lymphadenopathy, abdominal pain and aphthous ulcers. 13,17 Whereas Rilonacept, a soluble receptor, is more indicated in CAPS. In a placebo-controlled study, the disease activity score decreased by 84% in patients receiving Rilonacept, compared with those receiving placebo (13%).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical use of this bioagent in MKD has been approved with satisfactory results leading to a disappearance or a significant reduction in the severity of MKD features, including fever, lymphadenopathy, abdominal pain and aphthous ulcers. 13,17 Whereas Rilonacept, a soluble receptor, is more indicated in CAPS. In a placebo-controlled study, the disease activity score decreased by 84% in patients receiving Rilonacept, compared with those receiving placebo (13%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as discussed below, specific missense mutations S242R and E244K, involving this region of interest, cause the AID named "pyrinassociated autoinflammation with neutrophilic dermatosis" (PAAND) (33). In the meanwhile, the homozygous pathogenic variant S208T has been observed in children with a different clinical phenotype characterized by arthralgia, lymphadenopathy, purpuric rash, and infiltrates in bone marrow (14,34,35). It has been suggested that the S208 amino acid is not so central for pyrin inactivation than S242 (14).…”
Section: Region Of Interest For 14-3-3 Binding (93-369): S208 and S24...mentioning
confidence: 99%
“…It has been suggested that the S208 amino acid is not so central for pyrin inactivation than S242 (14). However, both patients with PAAND and homozygous S208T variants show increased IL-1b and IL-18 serum levels (14, [34][35][36]. In summary, pathogenic variants in the region of interest between PYD and B-box prevent PKN1/2 from phosphorylating pyrin, preventing the binding of 14-3-3 and leading to pyrin hyperactivation.…”
Section: Region Of Interest For 14-3-3 Binding (93-369): S208 and S24...mentioning
confidence: 99%
See 1 more Smart Citation
“…Заболевание описано в 2009 г., начинается, как правило, в раннем детском возрасте (известны отдельные случаи и более позднего начала) и проявляется хроническим рецидивирующим мультифокальным остеомиелитом, пустулезной кожной сыпью, поражением легких и центральной нервной системы. Имеется возможность генетической диагностики (выявление мутаций гена ILIRN) [28]. ХНО возможен еще при одном генетическом аутовоспалительном заболевании -синдроме PAPA (pyogenic arthritis, pyoderma gangrenosum, acne) -аутовоспалительный синдром, характеризующийся комбинацией стерильного эрозивного артрита, осложненных акне и гангренозной пиодермии, обусловленный мутациями гена белка PSTPIP1.…”
Section: Reviewunclassified